Situações didáticas no ensino de geometria com o aplicativo GeoGebra - Ramiro, Leandro [UNESP] (2014)
This work has as an objective to discuss the importance of demonstrations in teaching basic mathematics. There has been a long time that this topic is highlighted in the guiding documents of basic education (PCN and Official Curriculum), but in practice we have not found materials or activities that effectively guide teachers on how to implement logicaldeductive argumentation in the classroom. Concomitantly we found in Mathematics classes passivity on the part of most students in tackling the problems that are offered to them, in this way, based on the Theory of Didactic Situations as formulated by Guy Brouseau, and exploring the technological resources available at schools we propose activities that can be used in classrooms related to the geometry to be developed using the GeoGebra software. The activities are intended to bring the student to interact in an autonomous way with the concepts and properties involved and enable them in the development of conjectures and arguments on observed facts and check the results by means of dynamic movements that the software allows. We present a review of contents linked to movements in the plan: congruences, isometries, similarities and homotheties, necessary to the understanding of the proposed topic. Finally, we conducted an interview with a group of four school teachers in order to know their opinion about the proposed activities, their relationship with the new technologies and their interest in continued education